2009
DOI: 10.1097/ncn.0b013e3181a91b90
|View full text |Cite
|
Sign up to set email alerts
|

The Multimethod Evaluation of a Nursing Information System in Taiwan

Abstract: The purpose of this study was to evaluate the impact of a nursing information system on nurses' daily practice. A multimethod evaluation was used that combined both quantitative and qualitative approaches to explore the influence of this technology from different perspectives. The data collection methods included the following: an evaluation scale of the system function, focus group interviews about the users' experiences, and work sampling observation of their work pattern. The data were collected from Octobe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Moreover, after 1 year of using the system, for both day and evening shifts, the nurses' time spent on indirect care and unit-related activities during time 2 was less, but the time spent on documentation was more during time 2 than during time 1. Another study 16 showed that the day nurses spent more time on unit-related and personal activities, the evening nurses spent more time on direct care, and the night nurses spent more time on documentation and indirect care.…”
Section: Impact Of Information Systems On Nursing Activity Patternsmentioning
confidence: 97%
See 3 more Smart Citations
“…Moreover, after 1 year of using the system, for both day and evening shifts, the nurses' time spent on indirect care and unit-related activities during time 2 was less, but the time spent on documentation was more during time 2 than during time 1. Another study 16 showed that the day nurses spent more time on unit-related and personal activities, the evening nurses spent more time on direct care, and the night nurses spent more time on documentation and indirect care.…”
Section: Impact Of Information Systems On Nursing Activity Patternsmentioning
confidence: 97%
“…5,16,20,21,[24][25][26] The findings were categorized into themes to provide feedback not obtained by the questionnaires on CIS use and were used as a reference for information system evaluation. One study reported nurses' experiences of using a BCMA; they commented it was easier to find patient and drug information and that the system could prevent physicians' illegible handwriting or errors in transcribing prescriptions, although the nurses had more concerns about checking on the computer whether they might have missed a medication dose or have been unaware of the expiration date of the medication order.…”
Section: Evaluation Of Users' Experiences From Interviewsmentioning
confidence: 99%
See 2 more Smart Citations
“…This feedback should cover areas of overall user experience such as task performance or user satisfaction. 14 Evaluations using multiple evaluation methods provide a better overview for system designers and developers 15 ; therefore, this study used several measured methods and then triangulated between them to investigate the acceptance of online courses by new healthcare employees. The purpose was to identify factors related to online learning outcomes and to offer references for designing better orientation programs.…”
mentioning
confidence: 99%